An Experimental Analysis of Lean Binary Mixture Segregation in a Continuous Liquid Fluidized Bed - S. Narasimha Reddy; M. Venkata Ratnam (International Journal of Chemical Engineering)
This study examined the phenomenon of particle segregation in lean-phase binary mixtures, with a specific focus on the effect of particle size variations while flowing over a continuous liquid fluidized bed (LFB). The experimental configuration included a cylindrical column with a 72 mm internal diameter and 3 m vertical height. The binary mixture considered for this investigation was made up of solid materials that were rich in flotsam and jetsam. The study encompassed various factors, including liquid velocity, solid feed rate, and feed composition, in order to examine the separations containing flotsam and jetsam. A segregation index was calculated for each of the various combinations. On the other hand, the fluidization of the blend consisting of two solid components displayed notable differences in its behavior when compared to the reported effects of particle separation in any of the mixtures. Empirical correlations have been employed to establish relationships between variables, particularly with respect to solid entrainment and top and bottom product purity levels.